Depression Following Operative Treatments for Achilles Ruptures and Ankle Fractures. (December 2021) - Davison, Reid; Daniel, Jean-Philippe A.; Idarraga, Alexander J.; Perticone, Kathryn M.; Lin, Johnny; Holmes, George B.; Lee, Simon; Hamid, Kamran S.; Bohl, Daniel D.
Background: The sudden and debilitating nature of lower extremity injuries can trigger mood disturbances, including major depressive disorder. Methods: This prospective study enrolled patients undergoing operative repair of ankle fractures and Achilles ruptures and followed them for 1 year postoperatively. The validated Patient Health Questionnaire (PHQ-9) for depressive symptoms was administered at the preoperative visit and at postoperative weeks 1, 2, 4, 8, 16, 24, 32, 40, and 52. PHQ-9 is scored 0 to 27, with higher values indicating greater depression symptoms. Results: Fifty-eight patients completed 1 year of follow-up. The mean PHQ-9 score was 2.7 (range, 0-20) at the preoperative visit, peaked at postoperative week 1 (4.9; range, 0-16), and reached its low at postoperative week 52 (0.8; range, 0-7). Cumulative incidences of depressive symptoms during the first year following surgery were 51.7% for at least mild depression, 22.4% for at least moderate depression, and 6.9% for severe depression. A history of mental health disorder and the inability to work during the period of postoperative immobilization were independently associated with greater depressive symptoms. Conclusion: The majority of patients undergoing operative treatment of Achilles ruptures and ankle fractures develop postoperative symptoms of mild to moderate depression that normalize after several months. Patients with a history of mental health disorder or who cannot work while immobilized postoperatively are at greatest risk. Level of Evidence: Level II, prospective cohort study.